PENGUATAN PEMBELAJARAN EKOLOGI TUMBUHAN MELALUI PRAKTEK KULIAH LAPANGAN DI TAMAN SEWAKA DHARMA KOTA DENPASAR - I Wayan Suanda; Kadek Intan Rusmayanthi; I Kadek Febriandika Narakusuma (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2026)
Improving the quality of learning requires innovative and creative efforts to bring students closer to the object directly so that it is easy to learn and understand. Plant ecology is one of the courses that requires direct introduction in the field in the form of field lecture practice. Field Lecture Practice (PKL) is carried out to bring students closer to actual conditions through direct observation in the form of observation, , discussion and finding solutions as a form of desire to know the actual condition. The purpose of this study is to identify the types, local names, Latin names and vegetation of plants in the Taman Sewaka Dharma Denpasar area. The plants in Taman Sewaka Dharma Denpasar are quite varied from herbs, shrubs and trees arranged according to their vegetation. The presence of plants in this park is not only for shade, research, education but also as ceremonial materials. These plants are arranged in such a way based on the vegetation to create a beautiful, beautiful, shady and pleasant atmosphere.